Efecto antimicrobiano del propóleo sobre Streptococcus mutans. Revisión sistemática de la literatura (2024)
To control dental caries, various therapies are used; However, alternatives are emerging for natural products with properties that inhibit the development of cavities caused by bacteria, such as propolis, a bee product.